Mad puns and French poets: visual-verbal punning and 'l'art des fous' in Apollinaire's Calligrammes - Shingler, Katherine (Edinburgh University Press, 2014)
This article examines the use of visual-verbal punning structures in Guillaume Apollinaire's calligrammes, or visual poems. It considers how Apollinaire's mobilization of these punning structures may have emerged out of an interest in ‘l'art des fous’ (art and creative writing by the mentally ill, in which punning was a recurring feature), in psychiatric discourses which insisted on a link between punning and irrationality, and in the work of Jean-Pierre Brisset, whose nonsensical, pun-based theories of evolution made him a living embodiment of that link. It argues that for Apollinaire, the calligramme was an attempt to represent the structures of thought – unfettered, irrational thought – which could not be captured by linear discourse. The article situates this aspect of the calligrammes within the broader context of Apollinaire's primitivism, as expressed in his art criticism, before considering the continuity between Apollinaire's engagement with ‘l'art des fous’ and that of Breton, exploring the ethical implications of an aestheticizing approach to the ‘mad’ or ‘primitive’ work of art.